2021
DOI: 10.1136/bjophthalmol-2020-318717
|View full text |Cite
|
Sign up to set email alerts
|

Foveal structure and visual function in nanophthalmos and posterior microphthalmos

Abstract: Background/aimsThe reason for visual impairment in patients with nanophthalmos and posterior microphthalmos is not completely understood. Therefore, this study aims to investigate foveal structure, and the impact of demographic, clinical and imaging parameters on best-corrected visual acuity (BCVA) in these conditions.MethodsSixty-two eyes of 33 patients with nanophthalmos (n=40) or posterior microphthalmos (n=22), and 114 eyes of healthy controls with high-resolution retinal imaging including spectral-domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…As a proxy for AL, 52 54 refractive status expressed as SE was associated with FC, with myopic refractive status showing steeper foveas than hyperopic refractions. In the largest analysis of OCT-derived MC to date using multivariable multilevel regression (adjusting for age, sex, ethnicity, refractive error, IOP, VA, corneal astigmatism and fluid intelligence) Müller et al 8 (unpublished data, 2022) found that ethnicity and refractive error had the strongest association with MC (i.e., flatter MC with every D increase in refractive error, and steeper MC in black, Asian, and other ethnic groups when compared with whites). We have shown that steeper MC are associated with steeper FC.…”
Section: Discussionmentioning
confidence: 99%
“…As a proxy for AL, 52 54 refractive status expressed as SE was associated with FC, with myopic refractive status showing steeper foveas than hyperopic refractions. In the largest analysis of OCT-derived MC to date using multivariable multilevel regression (adjusting for age, sex, ethnicity, refractive error, IOP, VA, corneal astigmatism and fluid intelligence) Müller et al 8 (unpublished data, 2022) found that ethnicity and refractive error had the strongest association with MC (i.e., flatter MC with every D increase in refractive error, and steeper MC in black, Asian, and other ethnic groups when compared with whites). We have shown that steeper MC are associated with steeper FC.…”
Section: Discussionmentioning
confidence: 99%